International Business Strategy in Selling Korean Pop Music: A Case Study of SM Entertainment - Annisa Pratamasari (Global Strategis, 2016)
In this paper, I argue that some entertainment companies of South Korea offer a distinctive business strategy in this globalized world; thus, they can widen their market share, increase profits, and sharpen their competitive edge. SM Entertainment,which is one of the Hallyu Wave pioneers in music industry, has showed its distinct way to succeed in the currently saturated market of idol groups in South Korea. Choosing Hallyu Wave from international business perspective as the main topic of this writing was due to its increasing importance in music industry and its growing influence in South Korean government policies. Therefore, I shall descriptively address the strategies formulated by SM Entertainment to compete in the domestic and international music industry from its way to groom their idol groups to its way to ‘sell’ them.This paper offers some business strategies of SM Entertainment of which some other companies could learn from; namely the distinct traineeship system, successful B2C strategy, and profitable B2B cooperation.